Potential of low application rate combinations of three chitin synthesis inhibitor insecticides with spinosad for the control of Sitophilus oryzae on stored wheat. (January 2022) - Gad, Hassan A.; Al-Anany, Mohamed S.; Atta, Ayman A.M.; Abdelgaleil, Samir A.M.
Abstract: Insecticidal activities of spinosad and chitin synthesis inhibitors (CSIs) have been individually assessed against some stored product insects, but the efficacy of their combinations against stored product insects was not previously reported. Thus, bioassays were conducted to evaluate spinosad and three CSIs (chlorfluazuron, hexaflumuron and lufenuron) at low application rates as grain protectants, alone and in binary mixtures, against Sitophilus oryzae on stored wheat. The effect of individuals and binary mixtures on mortality of S. oryzae adults, progeny production and weight loss of wheat grains were determined. The individual treatments with spinosad (0.5 mg/kg), and chlorfluazuron, hexaflumuron and lufenuron (1.0 mg/kg) induced 63.0, 33.6, 35.2 and 34.1% mortalities of S. oryzae adults, respectively, after 21 days of treatment. The binary mixtures of spinosad with CSIs caused higher mortality of S. oryzae adults than the individual treatments of CSIs or spinosad after 7 and 14 days of treatment. Significant reduction of S. oryzae progeny was observed in all treatments. The binary mixture (0.5 mg/kg of spinosad + 1.0 mg/kg of chlorfluazuron) caused complete inhibition of progeny for 90 days. Similarly, grain damage caused by S. oryzae was significantly decreased in binary mixture treatments at high application rates. Additionally, the combined treatments had no adverse effect on seed germination after 90 days of treatment. These findings demonstrate that the binary mixtures of spinosad with CSIs might be applied to protect wheat grains against S. oryzae as alternatives to conventional neurotoxic insecticides. Highlights: Introducing novel crop protectants with different modes of action is essential to reduce insect resistance. Control of stored product insects with low application rates of crop protectants decreases toxic residues in commodities. Combinations of spinosad/chitin synthesis inhibitors at low application rates gave satisfactory control of S. oryzae. Binary mixtures of spinosad and chlorfluazuron induced complete protection of wheat grains S. oryzae for 90 days.